До моделювання якісного та кількісного складу стічних вод гальванічних виробництв - Регуш, А. Я.; Тихонова, І. А. (Видавництво Державного університету “Львівська політехніка”, 1999)
In work some features of clearing of waste water galwanic of manufacture; from ions of heavy metals are considered. The influence of initial concentration presence of organic substances and other on removal of heavy metal hydroxides ii specified.
Keywords: 628.54